Peningkatan Kualitas Kemasan Produk menggunakan Mesin Pres Segel Plastik Otomatis di Komunitas UMKM Shingkara Kecamatan Singosari Kabupaten Malang - Zakki Fuadi Emzain; Nanang Qosim; Ahmad Hanif Firdaus; Lisa Agustriyana; Muhammad Akhlis Rizza (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Micro, Small, and Medium Enterprises (UMKM) are one of the driving forces of the economy in a local area as well as a booster for the community's welfare. One of the obstacles often faced by the Shingkara UMKM community in Singosari District, Malang Regency is the lack of quality product packaging that still uses manual tools and is not optimal in creating marketing content. This community service aims to provide automatic plastic seal press machines and training on marketing content creation for micro-business actors in the Shingkara UMKM community so that it is expected to increase partners' competitiveness. The stages of community service were observation and coordination, providing machines, handing over machines, holding training, and evaluation. The results of the community service activities showed that the training participants were enthusiastic and actively participated during the training. The quality of product packaging after using a plastic seal press machine has also improved, evidenced by a tighter and well-protected packaging seal. The copywriting training has also broadened the participants' knowledge about strategies for creating product marketing content by utilizing applications available on Android.